2018
DOI: 10.3389/fvets.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors Influencing Dog Owners' Intention to Vaccinate Against Rabies Evaluated Using Health Belief Model Constructs

Abstract: Ethiopia has one of the highest incidence levels of human rabies in Africa, with 3–7 deaths per 100,000 people annually. The country has no official rabies control programme, despite the availability of an effective canine vaccine to control rabies. To support effective rabies control, an understanding of the factors affecting dog owners' voluntary intentions to vaccinate their dogs is important. As such, this study examined factors influencing dog owners' intentions to vaccinate their dogs using the construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 33 publications
2
22
0
3
Order By: Relevance
“…The delivery of these activities has been proven beneficial not only to provide the community with accurate information on disease prevention, but to improve their attitude concerning dog vaccination and engagement with rabies surveillance [13,45,46]. A similar regression analysis also showed that education was positively associated with the owner's intention to vaccinate their dog [44]. For similar reasons, it is logical that dogs from areas with higher education levels show increased odds of rabies vaccination.…”
Section: Variablementioning
confidence: 93%
See 2 more Smart Citations
“…The delivery of these activities has been proven beneficial not only to provide the community with accurate information on disease prevention, but to improve their attitude concerning dog vaccination and engagement with rabies surveillance [13,45,46]. A similar regression analysis also showed that education was positively associated with the owner's intention to vaccinate their dog [44]. For similar reasons, it is logical that dogs from areas with higher education levels show increased odds of rabies vaccination.…”
Section: Variablementioning
confidence: 93%
“…It is necessary for this unfounded belief to be addressed via educational campaigns, since many young animals still remain at risk for months, even while the vaccine has been proven to be both safe and effective in puppies [47]. The deterrent effect of distance on attendance to healthcare facilities has been previously reported [48,49], in addition to the specific effect of distance on attendance to static vaccination clinics [12,44]. However, in this study, the effect of distance on absolute coverage was found to be insignificant.…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found to be inversely related to perceived barriers such as the distance of the owners' residence from vaccination centre and ease of dog transportation. 8 WHO mentions that vaccinating 70% of the dog population is sufficient to eliminate canine rabies. 9 PEP prevents virus entry into the central nervous system, which results in imminent death.…”
Section: Discussionmentioning
confidence: 99%
“…Analisis regresi linier dalam penelitian ini menggunakan uji t dan uji anova dengan hasil sebagaimana dicantumkan dalam Tabel 5-8. (2,5,6,9,11,20 (6,15,20). 3 .…”
Section: Analisis Regresi Linierunclassified